BS EN IEC 60068-2-87. Environmental Testing. Part 2-87. Tests-Test xx: UV-C Exposure of Materials and Components to Simulate Ultraviolet Germicidal Irradiation or Other Applications (2nd March 2023) - British Standards Institution,
No abstract available